2011
DOI: 10.1073/pnas.1016354108
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome proliferator-activated receptor-γ coactivator 1-α (PGC1α) is a metabolic regulator of intestinal epithelial cell fate

Abstract: Peroxisome proliferator-activated receptor-γ coactivator 1-α (PGC1α) is a transcriptional coactivator able to up-regulate mitochondrial biogenesis, respiratory capacity, oxidative phosphorylation, and fatty acid β-oxidation with the final aim of providing a more efficient pathway for aerobic energy production. In the continuously renewed intestinal epithelium, proliferative cells in the crypts migrate along the villus axis and differentiate into mature enterocytes, increasing their respiratory capacity and fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
124
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(133 citation statements)
references
References 45 publications
7
124
1
1
Order By: Relevance
“…Because HSF1 is required for several processes that involve normal cell proliferation, such as spleen cell proliferation following immunization (40), muscle regeneration (41), and postnatal growth in C57BL/6 mice (42), it is possible that PGC-1α induction by fasting in liver (4) and muscle (43) represses HSF1 to mediate some of the antiproliferative effects of fasting. These scenarios also may hold true in cancer cells, although the potential effect of PGC-1α on cancer cell growth and survival is controversial, with reports suggesting both positive (44,45) and negative (46)(47)(48)(49)(50) associations between PGC-1α activity and cancer cell survival [including a negative association in HepG2 cells (51)], depending on the cellular context and on PGC-1α expression levels. It thus is possible that PGC-1α effects in cancer depend on a balance between its ability to induce metabolic genes and oxidative stress-response genes, a property that may promote cancer growth, and its ability to repress HSF1 activity.…”
Section: Discussionmentioning
confidence: 99%
“…Because HSF1 is required for several processes that involve normal cell proliferation, such as spleen cell proliferation following immunization (40), muscle regeneration (41), and postnatal growth in C57BL/6 mice (42), it is possible that PGC-1α induction by fasting in liver (4) and muscle (43) represses HSF1 to mediate some of the antiproliferative effects of fasting. These scenarios also may hold true in cancer cells, although the potential effect of PGC-1α on cancer cell growth and survival is controversial, with reports suggesting both positive (44,45) and negative (46)(47)(48)(49)(50) associations between PGC-1α activity and cancer cell survival [including a negative association in HepG2 cells (51)], depending on the cellular context and on PGC-1α expression levels. It thus is possible that PGC-1α effects in cancer depend on a balance between its ability to induce metabolic genes and oxidative stress-response genes, a property that may promote cancer growth, and its ability to repress HSF1 activity.…”
Section: Discussionmentioning
confidence: 99%
“…Under conditions of stress, PGC1␣ is a potent stimulator of mitochondrial turnover and antioxidant activity. Recently, it was demonstrated that PGC1␣ is highly expressed within the intestinal epithelium in mice (17). A decrease in PGC1␣ within the intestinal epithelium of a patient with ulcerative colitis is thought to be a precursor of dysplastic changes (18).…”
Section: In the Unitedmentioning
confidence: 99%
“…Ultimately, this leads to activation of mitochondrial transcription factor A (TFAM), a nucleus-encoded transcription factor that moves to the mitochondria, promoting transcription of the mitochondrial genome. Until recently, no evidence of abnormal mitochondrial biogenesis in the intestine had been reported (17). To assess how PGC1␣ down-regulation affects mitochondrial biogenesis in the intestinal epithelium during experimental colitis, we evaluated its downstream mediators in the biogenesis pathway, which were similarly down-regulated ( Fig.…”
Section: Pgc1␣ Demonstrates a Bimodal Pattern Of Expression During Thmentioning
confidence: 99%
“…MIST1 can also repress myogenic differentiation by targeting the MyoD gene [8]. Similarly, PGC1a regulates enterocyte cell fate and protects against tumorigenesis [9].…”
Section: Do Homologues Exist For Scaling Factors In Cells With Similamentioning
confidence: 99%